PENGARUH APLIKASI IBA (indole -3- butyric acid) TERHADAP PENGAKARAN SETEK DUA BUKU VANILI (Vanilla planifolia Andrews) - Sugiyanti Sugiyanti; Yusnita Yusnita; Dwi Hapsoro; Agus Karyanto; Rusdi Evizal (JURNAL AGROTROPIKA, 2026)
Vanilla (Vanilla planifolia Andrews) is a high economic value plant within the Orchidaceae family (orchid family). Efforts to increase vanilla growth and production can be made through the application of auxins to stimulate root formation. The development of vanilla requires high-quality seedlings, as one of the indicators of successful propagation through cuttings is the formation of roots and the growth of shoots. The purpose of this research is to study the effect of various concentrations of IBA on the rooting of two-node vanilla cuttings. This study uses a completely randomized design (CRD) with 6 treatments, each repeated 3 times. The treatments in this experiment consist of: control (without IBA), 500 ppm IBA, 1000 ppm IBA, 1500 ppm IBA, 2000 ppm IBA, and 2500 ppm IBA. The observed variables include shoot length, number of opened leaves, number of primary roots, number of root tips, longest root length, fresh root weight, and dry root weight. The results showed that a concentration of 2000 ppm IBA was able to increase the number of primary roots, number of root tips, longest root length, fresh root weight, and dry root weight.